Early and late-onset preeclampsia: effects of DDAH2 polymorphisms on ADMA levels and association with DDAH2 haplotypes - Fernanda Santos Mendes; Marcelo Rizzatti Luizon; Ana Cristina dos Santos Lopes; Daniela Alves Pereira; Fernanda Cristina Gontijo Evangelista; Lara Carvalho Godoi; Luci Maria Dusse; Patrícia Nessralla Alpoim (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: To examine whether the DDAH2 promoter polymorphisms -1415G/A (rs2272592), -1151A/C (rs805304) and -449G/C (rs805305), and their haplotypes, are associated with PE compared with normotensive pregnant women, and whether they affect ADMA levels in these groups. Methods: A total of 208 pregnant women were included in the study and classified as early-onset (N=57) or late-onset PE (N =49), and as normotensive pregnant women (N = 102). Results: Pregnant with early-onset PE carrying the GC and GG genotypes for the DDAH2 -449G/C polymorphism had increased ADMA levels (P=0.01). No association of DDAH2 polymorphisms with PE in single-locus analysis was found. However, the G-C-G haplotype was associated with the risk for late-onset PE. Conclusion: It is suggested that DDAH2 polymorphisms could affect ADMA levels in PE, and that DDAH2 haplotypes may affect the risk for PE.